DOTA-Derivatives of Octreotide Dicarba-Analogs with High Affinity for Somatostatin sst2,5 Receptors - Pratesi, Alessandro; Ginanneschi, Mauro; Lumini, Marco; Papini, Anna M.; Novellino, Ettore; Brancaccio, Diego; Carotenuto, Alfonso (Frontiers in Chemistry, 2017)
In vivo somatostatin receptor scintigraphy is a valuable method for the visualization of human endocrine tumours and their metastases. In fact, peptide ligands of somatostatin receptors (sst’s) conjugated with chelating agents are in clinical use. We have recently developed octreotide dicarba-analogues, which show interesting binding profiles at sst’s. In this context, it was mandatory to explore the possibility that our analogues could maintain their activity also upon conjugation with DOTA. In this paper, we report and discuss the synthesis, binding affinity and conformational preferences of three DOTA-conjugated dicarba-analogues of octreotide. Interestingly, two conjugated analogues exhibited nanomolar affinities on sst2 and sst5 somatostatin receptor subtypes.